Corneal neovascularisation following deep anterior lamellar keratoplasty for corneal ectasia: incidence, timing and risk factors. Issue 10 (13th May 2021) - Pellegrini, Marco; Scorcia, Vincenzo; Giannaccare, Giuseppe; Lucisano, Andrea; Vaccaro, Sabrina; Battaglia, Caterina; Yu, Angeli Christy; Bovone, Cristina; Busin, Massimo; Spena, Rossella
Abstract : Background: The purpose of this study was to evaluate the incidence, timing and risk factors of corneal neovascularisation (NV) after deep anterior lamellar keratoplasty (DALK) for corneal ectasia. Methods: This study included 616 eyes who underwent DALK between 2012 and 2020 in two tertiary referral centres. In one centre topical corticosteroids were discontinued after complete suture removal 1 year after surgery, whereas in the other they were discontinued 3–4 months after surgery. The presence and severity of corneal NV was ascertained based on slit lamp photographs. Potential risk factors for corneal NV were evaluated using the Cox proportional hazards model. Results: The cumulative incidence of corneal NV was 8.7% at 1 year after surgery and 13.2% at 5 years. Mean time interval from surgery to development of corneal NV was 12.8±16.2 months, with 68.9% of cases occurring before complete suture removal. Early discontinuation of topical steroids, older age and ocular allergy were associated with an increased risk of developing corneal NV (respectively, HR=2.625, HR=1.019, HR=3.726, all p<0.05). Conclusions: The risk of corneal NV is higher in the first year following DALK. Early discontinuation of topical steroids, ocular allergy and older age are significant predictors of corneal NV.